Epidemiology of Bovine Neosporosis in Relation to Socioeconomic, Demographic, and Transmissibility Factors in Dual-Purpose Production Systems in Colombia - Cesar A. Murcia-Mono; Sergio Falla-Tapias; Britney K. Cabrera-Ospina; Jahir O. Vargas-Domínguez; William O. Burgos-Paz (Epidemiologia, 2024)
Introduction: Bovine neosporosis represents a significant threat to reproduction and production in livestock systems worldwide. This disease is caused by the protozoan Neospora caninum, resulting in abortions of cows and neurological signs in newborn calves. This leads to significant economic losses, decreasing meat and milk production, especially in tropical regions. The infection has an endogenous and exogenous cycle of transmission involving dogs that shed the oocysts, with the highest transmission successes in humid areas. Similarly, there is a lack of knowledge about the epidemiological risk factors and management practices involved in the transmission success in tropical humid regions. Methods: In this sense, a cross-sectional epidemiological survey was conducted on 150 farms from 24 municipalities of the Huila area. A total of 360 cattle were sampled, and information about the production system was collected using a structured poll with 128 questions. Results: In these cattle, 53% (191/360) were positive for antibodies against Neospora caninum using ELISA. The logistic regression analysis using the information collected from the poll identified the presence of flooring type, water access, production systems, and feed management as risk factors. Among the protective factors were identified the geographical area, molasses supplementation, and biosecurity practices such as animal separation and access control. Discussion: This study identified for the first time the epidemiological risk factors associated mainly with the exogenous cycle of neosporosis. The present study contributes to the design of intervention strategies oriented to minimize the impact of parasitism in Colombian herds.